Protective Effect of Sika Deer (Cervus nippon) Velvet Antler Extract against Cisplatin-Induced Kidney and Liver Injury in a Prostate Cancer PC-3 Cell Xenograft Model - Yujiao Tang; Meiqi Fan; Young-Jin Choi; Eun-Ju Choi; Sang-Ho Moon; Trishna Debnath; Yonghai Yu; Il Nam Lee; Eun-Kyung Kim (Journal of Chemistry)
We previously discovered the antioxidant and antiprostate cancer effects of antler extract (AE), but whether it inhibits cisplatin- (Cis-) induced toxicity has not been investigated. In this study, the effect of AE on Cis-induced side effects in the kidney and liver using 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide-based cytotoxicity and cell cycle assays in prostate cancer PC-3 cells in vitro is investigated. Furthermore, we used a xenograft mouse model of the same cells to examine the in vivo effects and mechanisms of action. Cis and Cis + AE treatment attenuated prostate cancer cell growth by inducing apoptosis in vitro. Cis + AE stimulated cleaved caspases 3, 7, and 9 and polyadenosine diphosphate ribose polymerase expression. Cis + AE treatment for 1 week significantly increased the superoxide dismutase and catalase antioxidant activity while thiobarbituric acid reactive substances decreased. The histopathological damage and tumor necrosis factor-α, interleukin- (IL-) 1β and IL-6, cyclooxygenase-2, and inducible nitric oxide synthase expression in the kidney and liver tissue decreased. Therefore, AE likely possesses antiprostate cancer activity and inhibits Cis toxicity.